Postural balance and fall risk in patients with systemic sclerosis: A cross-sectional study - Hazal YAKUT,; Sevgi ÖZALEVLİ,; Ahmet Merih BİRLİK, (Archives of Rheumatology, 2021)
Objectives: This study aims to assess postural balance, fall risk, and the relationship of these parameters with disease-related factors in patients with systemic sclerosis (SSc). Patients and methods: Thirty patients with SSc (6 males, 24 females; mean age 51.1±10.6 years; range 35 to 65) and 30 healthy subjects (6 males, 24 females, mean age 52.4±8.7 years; range 35 to 65) matched for age, sex and body mass index were included in this cross-sectional study conducted between September 2018 and November 2019. Postural balance was measured with Biodex Balance SystemTM (Biodex-BS), Berg Balance Scale (BBS), and Timed Up and Go (TUG) test. Individuals’ history of falls in the past year, functional capacity, lower limb muscles strength, pulmonary function, respiratory muscle strength, diffusion capacity, and dyspnea severity were evaluated. Results: The SSc group had postural balance impairment and a higher fall frequency than the control group. The SSc group had significantly higher sway index on postural stability (0.6±0.5), lower directional control score (42.1±8.0), and longer test duration (51.8±11.8) on limit of stability of Biodex-BS, lower BBS score (51.5±4.9), and longer test duration on TUG test (8.3±2.7) than control group (all p<0.05). Also, SSc group exhibited significantly lower functional capacity, limb muscles strength, pulmonary function, respiratory muscles strength, diffusion capacity, and higher dyspnea severity than control group (all p<0.05). The postural balance and fall frequency of SSc patients were significantly associated with functional capacity, lower limb muscles strength, pulmonary function, respiratory muscle strength, diffusion capacity, and dyspnea severity. Conclusion: Our results suggest that postural balance impairment and fall risk should be assessed as they appear to be important problems in patients with SSc. Furthermore, assessment of functional capacity, lower limb muscles strength, and lung involvement may highlight those with postural balance impairment and higher fall risk.